THRIFT SHOPPING DALAM PERSPEKTIF HUKUM DI INDONEISA DAN DAMPAKNYA TERHADAP UMKM: THRIFT SHOPPING DALAM PERSPEKTIF HUKUM DI INDONEISA DAN DAMPAKNYA TERHADAP UMKM - DINA NISA ULFIANA (CV Rewang Rencang, 2024)
ABSTRACT Thrift shopping, known as buying quality used goods at affordable prices, has become an important trend in society. In fact, even though some used goods have been banned for decades, the smuggling of these goods causes losses to the Indonesian state and violates existing laws and regulations. Apart from that, the rise of the second-hand goods business has reduced the absorption capacity of domestic clothing production. So the author is interested in researching how the regulations regulate the thrifting business, and the impact of the thrifting business on sustainable business and how the Government can overcome this. This research was conducted using a normative juridical approach. The research results show that according to regulations, the import and distribution of used clothing is actually prohibited by law in Indonesia due to several laws and regulations. However, thrift shopping activities remain widespread due to high consumer demand and weak law enforcement. Second-hand shopping activity is still widespread. This activity has a negative impact on local clothing MSMEs because they have to compete with cheaper imported products. It is estimated that imports of used clothing will reduce the MSME market share by 12-15%. The main obstacles in overcoming thrift shopping are high consumer demand, weak law enforcement, and still limitations in monitoring and evaluating the ban on importing used clothing. Government initiatives include strengthening border security, confiscation and demolition. Keywords: Thrift shopping, Indonesian law, MSMEs, regulations.